2011
DOI: 10.1103/physrevb.84.241404
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in potassium-doped graphene: The effects of electron-phonon interactions, dimensionality, and adatom ordering

Abstract: Graphene phonons are measured as a function of electron doping via the addition of potassium adatoms. In the low doping regime, the in-plane carbon G-peak hardens and narrows with increasing doping, analogous to the trend seen in graphene doped via the field-effect. At high dopings, beyond those accessible by the field-effect, the G-peak strongly softens and broadens. This is interpreted as a dynamic, non-adiabatic renormalization of the phonon self-energy. At dopings between the light and heavily doped regime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
84
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 34 publications
(85 reference statements)
13
84
2
Order By: Relevance
“…While this model is now has strong experimental support, interesting inconsistencies remain, for example the reported calcium isotope effect [43]. Furthermore the large electron-phonon coupling between * electrons and Cxy phonons measured in ARPES [51,52], is in contrast with DFT predictions despite being consistent with linewidths measured in Raman Spectroscopy [50,65], an effect also shown to evolve in monolayer and few layer graphene with increasing doping [66]. However despite these interesting discrepancies more recent ARPES reconcile the picture arising from DFT [54,45].…”
Section: Discussioncontrasting
confidence: 48%
“…While this model is now has strong experimental support, interesting inconsistencies remain, for example the reported calcium isotope effect [43]. Furthermore the large electron-phonon coupling between * electrons and Cxy phonons measured in ARPES [51,52], is in contrast with DFT predictions despite being consistent with linewidths measured in Raman Spectroscopy [50,65], an effect also shown to evolve in monolayer and few layer graphene with increasing doping [66]. However despite these interesting discrepancies more recent ARPES reconcile the picture arising from DFT [54,45].…”
Section: Discussioncontrasting
confidence: 48%
“…An example of the latter can be depicted by different experimental and theoretical studies reported with a wide range of different G-line positions and line-shapes between ∼1400 cm −1 and ∼1600 cm −1 : that is, at ∼1500 cm −1 [2], between 1400 cm −1 and 1550 cm −1 [17], 1534 cm −1 [69], 1547 cm −1 [21], 1420 cm −1 and 1582 cm −1 [76]. The incongruity of these results is directly related to an incomplete intercalation as reported recently in potassium doped graphene [12] and stage I GICs [70]. On top of this, defect modulation of GICs is crucial when studying the G-line response from superconducting GICs faces.…”
Section: Superconductivity In Stage I Gic and Implications For Interccontrasting
confidence: 49%
“…Common intercalants are alkali-metals (K, Li, Cs, Rb), alkali-earth-metals (Be, Ca, Ba), rare-earth elements or molecular groups such as FeCl 3 , AsF 5 , H 2 SO 4 , HNO 3 , etc. All the above form different tri-dimensional macro-molecules, each one with intrinsic electronic, physical and chemical properties [2,3,[9][10][11][12][13][14][15]. The properties that distinguish every GIC directly depend on the specific chemical species which occupy the carbon interlayer space.…”
mentioning
confidence: 99%
“…Ideally, the reactivities of KC 8 and KC 24 should fall within these Fermi energy shifts for partial and complete charge transfer. Potassium GICs were produced via the vapour transport method, 20 to give the corresponding characteristic bronze stage 1 KC 8 and steel blue stage 2 KC 24 compounds (Fig. 1B).…”
Section: Potassium Graphenide Experimentsmentioning
confidence: 99%
“…Fractions of the supernatant were then taken for subsequent reactions. KC 8 and KC 24 were made by CAH and PLC, respectively, using the vapour transport method from natural flake graphite (Madagascar) 20 and were confirmed to be phase pure by X-ray diffraction (within the limits of the measurement). For each experiment, 20 mL, NMP (anhydrous grade, 99.5%, further dried by 4 Å molecular sieves, both purchased from SigmaAldrich, UK), was added to 10 mg KC x in a 100 mL Young's tap Schlenk tube.…”
Section: Preparation Of Charged Carbon Polyelectrolytesmentioning
confidence: 99%